Development of 316L-0.3Y2O3 ODS steels by selective laser melting - Liang, Penghui (2019)
Oxide-Dispersion-Strengthened (ODS) steel has developed into one of the most promising structural materials for advanced nuclear reactors. However, the traditional preparation method of ODS steel, powder metallurgy (PM), has many problems and defects in the manufacturing process. As such, we attempt to use an additive manufacturing technology, selective laser melting (SLM), to print out the desired ODS steel.